Circulating fibrocytes are not disease-specific prognosticators in idiopathic pulmonary fibrosis. Issue 1 (22nd July 2021) - Stewart, Iain D.; Nanji, Henry; Figueredo, Grazziela; Fahy, William A.; Maher, Toby M.; Ask, Antje J.; Maharaj, Shyam; Ask, Kjetil; Kolb, Martin; Jenkins, Gisli R.
A number of previous studies have observed greater levels of circulating fibrocytes in interstitial lung disease compared to healthy controls, and suggest a prognostic role in idiopathic pulmonary fibrosis (IPF) [1–4]. Fibrocytes are circulating mesenchymal progenitor cells that differentiate into tissue specific fibroblasts and contribute to multiple wound healing processes, including secretion of inflammatory cytokines, contractile wound closure and promotion of angiogenesis [5]. However, the contribution of fibrocytes to the pathogenesis of progressive pulmonary fibrosis remains unclear and clinical observations require independent validation in prospective cohorts. In people with idiopathic pulmonary fibrosis, circulating fibrocytes ≥2.2% were associated with a greater risk of mortality over a median 3 years of follow-up, but were not associated with disease-related decline in lung function or short-term progression. https://bit.ly/3bWydwQ